Effective playing environment management improving the quality of services for Daycare - Yanti, Sefri; Munastiwi, Erni; Uminar, Ajeng Ninda (Universitas Islam Negeri Raden Intan Lampung, 2022)
The application of effective playground environment management can improve the quality of daycare (TPA) services. This study aims to describe the effective management of the playground environment in enhancing the quality of services at Daycare. The research method uses a qualitative descriptive approach. The study's data sources were one manager, five educators, and two accompanying teachers. Data collection techniques using documentation, observation, and interviews. The data analysis technique uses data triangulation techniques through data reduction, presentation, and conclusion drawing. The results and findings showed that effective playground environment management improves the quality of services implemented at was through several stages, including the planning, implementation, and evaluation stages. The planning stage determines business opportunities, meeting facilities and infrastructure standards, learning strategies, the quality of educators for education staff, and service programs. The implementation stage is done by implementing an integrated service program through holistic services. Furthermore, the evaluation stage is done by reporting the implementation and evaluation of activities in the teacher council and foundation meeting forums held in monthly meetings. This management can be used as a reference as a means of effective play management for children's play.